Nucleated red blood cells as a novel biomarker in the diagnosis and prediction of sepsis severity in children - Li, Hongdong; Tu, Qianqian; Feng, Kun; Cheng, Jie; Zou, Zhiping; Li, Shaojun; Tan, Liping (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Sepsis is a vitally serious disease leading to high mortality. Nucleated red blood cells (NRBCs) are present in some noninfectious diseases, but the relationship between NRBCs and sepsis in children remains unknown. The purpose of this study was to compare the clinical characteristics and outcomes of sepsis with positive NRBCs and negative NRBCs in children, and to further explore whether the count of NRBCs has a relationship with the severity of sepsis. Methods We enrolled children with sepsis who were admitted to the Children’s Hospital of Chongqing Medical University between January 2020 and December 2022. The children’s clinical data, laboratory data and outcomes were recorded and analyzed. Results One hundred and fifteen children met the inclusion criteria in our study. Compared to negative NRBCs patients, the C-reactive protein, alanine transaminase, urea nitrogen values, mortality rate and length of hospitalization were found to be significantly increased, while platelet counts, and hemoglobin were significantly decreased in sepsis patients with positive NRBC (P < 0.05). Receiver operating characteristic (ROC) curves analysis showed that the optimal cutoff value of the NRBC count in the diagnosis of severe sepsis was 3, with a sensitivity of 87.5% and specificity of 94.9%. The area under the ROC curve was 0.877 (95% CI: 0.798-0.957). Discussion These findings demonstrated that NRBC count has the potential to be a biomarker for the diagnosis of sepsis in children, especially an NRBC count greater than 3, which may predict the severity and poor prognosis in children suffering from sepsis.